Integrated Isoform Sequencing and Dynamic Transcriptome Analysis Reveals Diverse Transcripts Responsible for Low Temperature Stress at Anther Meiosis Stage in Rice - Qu, Zhaojun; Jia, Yan; Duan, Yuyang; Chen, Hongyang; Wang, Xinpeng; Zheng, Hongliang; Liu, Hualong; Wang, Jingguo; Zou, Detang; Zhao, Hongwei (Frontiers in Plant Science, 2021)
Low temperatures stress is one of the important factors limiting rice yield, especially during rice anther development，and can cause pollen sterility and decrease grain yield. In our study, low-temperature stress decreased pollen viability and spikelet fertility by affecting the sugar, nitrogen and amino acid contents of anthers. We performed RNA-seq and ISO-seq experiments to study the genome-wide transcript expression profiles in low-temperature anthers. A total of 4859 differentially expressed transcripts were detected between the low-temperature and control groups. Gene ontology enrichment analysis revealed significant terms related to cold tolerance. Hexokinase and glutamate decarboxylase participating in starch and sucrose metabolism may play important roles in the response to cold stress. Using weighted gene co-expression network analysis, nine hub transcripts were found that could improve cold tolerance throughout the meiosis period of rice: Os02t0219000-01 (interferon-related developmental regulator protein), Os01t0218350-00 (tetratricopeptide repeat-containing thioredoxin), Os08t0197700-00 (luminal-binding protein 5), Os11t0200000-01 (histone deacetylase 19), Os03t0758700-01 (WD40 repeat domain-containing protein), Os06t0220500-01 (7-deoxyloganetin glucosyltransferase), Pacbio.T01382 (sucrose synthase 1), Os01t0172400-01 (phospholipase D alpha 1 ), and Os01t0261200-01 (NAC domain-containing protein 74). In the PPI network, the protein minichromosome maintenance 4 (MCM4) may play an important role in DNA replication induced by cold stress.